Az önámító költő és a rossz világa: (Kosztolányi Dezső: Nero, a véres költő) - Mohai V., Lajos (Studia Litteraria, 2018)
The novel, titled Nero, the Bloody Poet, written by Kosztolányi in 1922, is about the deviant human being; the portrayal of a deteriorating era serves as background for the portrait of a degenerate personality possessed by the demon spirit – the amateur poet and the disturbed dictator at the same time. it is about a man who submitted himself to, and became the ambassador of, the evil in the world. However, the manifestation of evil cannot be solely related to the main protagonist of the novel. As nero was left alone to make his way in life the novel can also be accounted for as a story of value dissolution. Kosztolányi deliberately put evil in the centre of discussion in his novel and identified it with the fundamental problem of human existence. The reader witnesses several aspects and stages of the distortion of nero’s character until finally distinguishes the inexperienced poet from the oppressive emperor. The use of the framework of the theory of value systems and the incorporation of Hermann Broch’s conception of kitsch might open up new perspectives for the analysis of the novel in the future.